Peran Komunikasi dan Musyawarah dalam Menangani Konflik Hubungan Industrial: Studi Kasus PHK di Smartfren Telecom Tbk - Hilma Harmen; Dina Sarah Syahreza; Luhut Manurung; Muhammad Umair Yazid; Samuel Indra Sitorus; Windah Frawyta Lestari Sinaga; Wulan Erdianti Putri; Yurida Aulia (MES Bogor, 2024)
The purpose of writing this article is to analyze the case of unilateral termination of employment (PHK) at PT Smartfren Telecom TBK sought by the trade union association. This research method uses a qualitative research method that involves collecting and analyzing data from a variety of source articles, also known as the literature review method. In the telecommunications industry, the role of communication and deliberation is important in overcoming challenges such as layoffs. This study highlights the importance of effective communication between company management and employees to properly manage layoffs. Empathetic and clear communication helps build better relationships and reduce conflict. In addition, deliberation allows different parties to participate in finding fair and sustainable solutions. With this approach, companies can better manage layoffs, while taking into account the interests and welfare of employees.